Robust CERN LHC Higgs boson search in weak boson fusion - Alves, A.; Eboli, O.; Plehn, T.; Rainwater, D. (American Physical Soc, 2004)
We demonstrate that a CERN LHC Higgs boson search in weak boson fusion production with subsequent decay to weak boson pairs is robust against extensions of the standard model or minimal supersymmetric standard model involving a large number of Higgs doublets. We also show that the transverse mass distribution provides unambiguous discrimination of a continuum Higgs signal from the standard model.